Lithospermic acid targeting heat shock protein 90 attenuates LPS-induced inflammatory response via NF-кB signalling pathway in BV2 microglial cells - Jie Guo; Chen-guang Li; Feng-yi Mai; Jing-rong Liang; Ze-hao Chen; Jiao Luo; Ming-chao Zhou; Yu-long Wang; Wen-tao Yang (Immunologic Research, 2025)

Mass cytometry revealed the circulating immune cell landscape across different Suzuki stages of Moyamoya disease - Chenglong Liu; Peicong Ge; Bojian Zhang; Liujia Chan; Yuheng Pang; Chuming Tao; Junsheng Li; Qiheng He; Wei Liu; Siqi Mou; Zhiyao Zheng; Zhikang Zhao; et al. (Immunologic Research, 2024)
Moyamoya disease (MMD) is a cerebrovascular disorder marked by progressive arterial narrowing, categorized into six stages known as Suzuki stages based on angiographic features. Growing evidence indicates a pivotal role of systemic immune and inflammatory responses in the initiation and advancement of MMD. This study employs high-dimensional mass cytometry to reveal the immunophenotypic characteristics of peripheral blood immune cells (PBMCs) at various Suzuki stages, offering insights into the progression of MMD. PBMC samples from eight patients with early-stage MMD (Suzuki stages II and III) and eight patients with later-stage MMD (Suzuki stages IV, V, and VI) were analyzed using high-dimensional mass cytometry to evaluate the frequency and phenotype of immune cell subtypes. We identified 15 cell clusters and found that the immunological features of early-stage MMD and later-stage MMD are composed of cluster variations. In this study, we confirmed that, compared to later-stage MMD, the early-stage MMD group exhibits an increase in non-classical monocytes. As the Suzuki stage level increases, the proportions of plasmacytoid DCs and monocyte-derived DCs decrease. Furthermore, T cells, monocytes, DCs, and PMN-MDSCs in the early-stage MMD group show activation of the canonical NF-κB signaling pathway. We summarized and compared the similarities and differences between early-stage MMD patients and later-stage MMD patients. There is a potential role of circulating immune dysfunction and inflammatory responses in the onset and development of MMD.

The expression of CD86 in CD3+CD56+ NKT cells is associated with the occurrence and prognosis of sepsis-associated encephalopathy in sepsis patients: a prospective observational cohort study - Sheng-long Chen; Xiao-yu Liu; Jun-hong Huang; Lu-hua Xian; Xu-sheng Li; Kang-rong Wang; Jing Li; Tian-cao Zhang; Guo-ge Huang; Xin-qiang Liu; Hong-ke Zeng; Mao-hua Zhou; et al. (Immunologic Research, 2023)

Potential therapeutic strategies for myocardial infarction: the role of Toll-like receptors - Sumra Komal; Nimrah Komal; Ali Mujtaba; Shu-Hui Wang; Li-Rong Zhang; Sheng-Na Han (Immunologic Research, 2022)

Activation of autophagy reverses gemcitabine-induced immune inhibition of RAW264.7 macrophages by promoting TNF-α, IL-6 and MHC-II expression - Shanshan Jiang; Rong Wang; Lu Han; Kudelaidi Kuerban; Li Ye; Shu Pan; Shengnan Li; Yongfang Yuan (Immunologic Research, 2021)
This research aims to investigate the effect of gemcitabine (GEM) on various activities and functions of macrophages. Phagocytosis, cell autophagy and reactive oxygen species (ROS) were analysed by laser scanning confocal microscope. The cell cycle status and major histocompatibility complex II (MHC-II) expression were examined by flow cytometry. Inflammatory cytokine secretion such as tumour necrosis factor α (TNF-α) and interleukin 6 (IL-6) was detected by Elisa assay. The expression of proteins was analysed by western blot method. The results revealed that GEM-induced immune inhibition of M1-type RAW264.7 macrophages activated by interferon-γ (IFN-γ) and lipopolysaccharide (LPS). We also found that GEM inhibited autophagy, as evidenced by the reduced formation of autophagosome-like vacuoles and autophagosomes. Further study showed that incubation of activated macrophages with the autophagy inhibitor 3-MA induced immune suppression. In contrast, treatment with the autophagy inducer trehalose (Tre) restored phagocytosis, TNF-α and IL-6 secretion, and MHC-II expression in GEM-induced immune-inhibited macrophages. GEM reduced immune effect of M1-type RAW264.7 macrophages via inhibiting TNF-α, IL-6 and MHC-II expression. Furthermore, activation of autophagy by Tre reversed GEM-induced immune inhibition of RAW264.7 macrophages.

The levels of DNGR-1 and its ligand-bearing cells were altered after human and simian immunodeficiency virus infection - Wen-Rong Yao; Dong Li; Lei Yu; Feng-Jie Wang; Hui Xing; Gui-Bo Yang (Immunologic Research, 2017)

EGCG induces G-CSF expression and neutrophilia in experimental sepsis - Wei Li; Andrew H. Wu; Shu Zhu; Jianhua Li; Rong Wu; John D’Angelo; Haichao Wang (Immunologic Research, 2015)